Evaluation of anhydrous ammonia applications in winter wheat - Wyckoff, Matthew R. (Kansas State University, 2012)
Research has shown that nitrogen fertilizer is needed most years to optimize winter wheat yields in Kansas. Anhydrous ammonia (AA) has long been a favorite N fertilizer of producers as it has proven to be a reliable and economical source of N. Anhydrous application methods and equipment have changed little over the past 70 years. Recently John Deere has developed their 2510 HSLD (2510H) anhydrous ammonia applicator designed to improve efficiency and performance in no-till systems. The 2510H is designed to be run at high speed with low soil disturbance and low draft. This is achieved by using a rolling coulter type injection unit, designed much like modern single disk opener grain drill units, to apply AA at relatively shallow depths. With this low soil disturbance design, topdress AA applications may also be possible. Due to the environmental risks associated with wheat production, many Kansas producers prefer an N management system that consists of a “starter” application at planting with the majority of the N fertilizer applied in the spring. This approach makes certain that the crop survives the winter before the investment in N is made and eliminates the potential for fertilizer N being lost over the winter months. It has not been feasible to use AA for topdressing in the past due to the damage to the growing crop from application with traditional knife style applicators. The first part of this research revisits traditional preplant AA application methods by evaluating proper unit spacing and the use of nitrification inhibitors as well as comparing these AA treatments to common topdress applications of N. Over three site years, few consistently significant advantages between unit spacing, use of nitrification inhibitor or N management method were found. Unit spacing did show a notable trend favoring 50 cm spacing. The second part of this research was a two-year experiment conducted with the objective of assessing the feasibility of topdressing with AA using the 2510H as compared with topdressing with granular urea. A number of factors such as application direction in relation to crop row, speed of application and timing as a function of crop development were examined to minimize crop injury and maximize crop yield. The initial 2010 study was promising, showing no significant yield loss topdressing with AA compared to topdressing with urea. The experiment was repeated at two locations in 2011. Results were mixed, indicated that soil conditions and the plants ability to recover from the AA application injury were important for the success of topdressing with AA. Lastly, an economic evaluation of the production economics of preplant and topdress AA was compared to the traditional practice of topdressing winter wheat with urea. Through evaluation of the agronomic and economic factors affecting the feasibility of uses of AA and the 2510H, three main conclusions can be made: 1. Preplant application of AA has no agronomic advantage and only a small economic advantage over topdressing with urea when yields are the same. 2. Topdressing with AA is agronomically feasible but is at an economic disadvantage when compared to topdressing with urea, due to the yield reduction associated with the AA method. 3. Further research focused on reducing yield loss with topdress AA applications is needed before this N management strategy can be promoted on a large scale.
Keywords: Wheat; Nitrogen; Anhydrous ammonia; Topdress; Preplant; Topdress anhydrous ammonia; Agronomy (0285)